2010
DOI: 10.1161/circgenetics.109.917443
|View full text |Cite
|
Sign up to set email alerts
|

A Common Variant at Chromosome 9P21.3 Is Associated With Age of Onset of Coronary Disease but Not Subsequent Mortality

Abstract: Background— Chromosome 9p21.3 (chr9p21.3) recently was identified by several genome-wide association studies as the genomic region most strongly associated with the risk of coronary artery disease. Within the chr9p21.3 locus, the single-nucleotide polymorphism rs1333049 has been demonstrated to be most strongly associated with susceptibility to developing coronary artery disease. However, the effect of rs1333049 on clinical outcomes in patients with established coronary disease has yet to be determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
4
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 27 publications
3
43
4
2
Order By: Relevance
“…Ассоциа-ция с ИБС была показана для rs1333049 в исследова-нии в США и Португалии, где СС генотип полимор-физма rs1333049 был ассоциирован с повышенным риском ИБС [12][13][14]. Кроме того, носители СС гено-типа имели повышенный уровень триглицеридов и холестерина в крови [15]. По данным Ellis, et al (2010) этот ОНП ассоциирован с ранним началом ИБС.…”
Section: Complex Evaluation Of the Significance Of Populational Genetunclassified
See 1 more Smart Citation
“…Ассоциа-ция с ИБС была показана для rs1333049 в исследова-нии в США и Португалии, где СС генотип полимор-физма rs1333049 был ассоциирован с повышенным риском ИБС [12][13][14]. Кроме того, носители СС гено-типа имели повышенный уровень триглицеридов и холестерина в крови [15]. По данным Ellis, et al (2010) этот ОНП ассоциирован с ранним началом ИБС.…”
Section: Complex Evaluation Of the Significance Of Populational Genetunclassified
“…По данным Ellis, et al (2010) этот ОНП ассоциирован с ранним началом ИБС. А согласно результатам, полученным Buysschaert, et al (2010) еще и с повторным ИМ и сер-дечной смертью после острого коронарного син-дрома [15,16].…”
Section: Complex Evaluation Of the Significance Of Populational Genetunclassified
“…Previously, we have reported that a common risk variant within the 9p21.3 risk region was associated with age of CAD onset but not subsequent mortality. 16 In the current study, we have investigated the association between risk variants at 1p13.3, 1q41, and 3q22.3 and cardiovascular outcomes in both individuals free of overt cardiovascular disease (CVD) at the time of recruitment and in patients with established CAD.…”
Section: Clinical Perspective On P 646mentioning
confidence: 99%
“…Previous research with whites, homozygous for the risk allele for rs1333049 compared to those with wild-type alleles, demonstrated a 2-5 years earlier onset of CHD (Ellis et al, 2010) and a strong association with 3-vessel disease in those with early onset CHD (Dondona et al, 2010). This supported previous findings that other SNPs in the same haplotype block (rs10757274, rs2383206, rs2383207, and rs10757278) were associated with premature CHD in whites (Helgadottir et al, 2007;Abdullah et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Studies differ in the selection of 9p21 SNPs and the definitions of early-onset disease but uniformly include few women or non-white populations. Chromosome 9p21 SNPs were correlated with early onset CHD in several white (Helgadottir et al, 2007;Abdullah et al, 2008;Meng et al, 2008;Ellis et al, 2010) and Chinese (Chen et al, 2009) populations but not in others (Broadbent et al, 2008;Dehghan et al, 2008). Approximately 25% of whites carry two copies of the 9p21 risk alleles with an estimated risk of early onset CHD that is twice that among individuals without these alleles (McPherson, 2010).…”
Section: Introductionmentioning
confidence: 94%